The impacts of the global pandemic on online learning in Vietnam - Bao, Dat (English Language Teaching Educational Journal, 2023)
The global outbreak of COVID-19 has caused tremendous disruptions in the field of education, including in Vietnam. In response to the ongoing pandemic, online learning has emerged as the primary mode of education delivery, transforming the traditional learning landscape. This article reports a study that adopts a combination of reflection and text-based research. The project explores the impacts of the pandemic on online learning in the new normal within the Vietnamese education system. The work focuses mainly on learning motivation, student engagement, and digital competence. While the pandemic has led to increased acceptance and utilization of online learning platforms, it has also presented challenges, including issues of digital inequality and limited social interaction. Findings suggest that the Vietnamese education system needs to adapt to fully harness the potential of online learning in the new normal.